(untitled) - Buckingham, Marcus (Boston, 2015)
That’s about to change. StandOut 2.0 is a revolutionary book and tool that enables you to identify your strengths, and those of your team, and act on them. The original edition of StandOut provided top-notch insights from one of the world’s foremost authorities on strengths, as well as access to a powerful, cutting-edge online assessment tool. StandOut 2.0 also includes the assessment and a robust report on your most dominant strengths. The report is easily exported so you can use it to present the very best of yourself to your team and your company.
Keywords: Thúc đẩy nhân lực,Employee motivation